Processual business and transaction in improbity action: limits and possibilities after amendments to law 13.964/2019 (Research, Society and Development, 2020)
The purpose of this article is to analyze the possibility of conducting a procedural convention in the context of administrative improbity actions, especially after the most recent legislative changes. The study goes through the analysis of the appropriateness of the transaction, within a current procedural and material context, concluding by the feasibility in specific procedural issues.